Dietary sodium chloride attenuates increased β-cell mass to cause glucose intolerance in mice under a high-fat diet. - Keigo Taki; Hiroshi Takagi; Tomonori Hirose; Runan Sun; Hiroshi Yaginuma; Akira Mizoguchi; Tomoko Kobayashi; Mariko Sugiyama; Taku Tsunekawa; Takeshi Onoue; Daisuke Hagiwara; Yoshihiro Ito; et al. (PLoS ONE)
Excessive sodium salt (NaCl) or fat intake is associated with a variety of increased health risks. However, whether excessive NaCl intake accompanied by a high-fat diet (HFD) affects glucose metabolism has not been elucidated. In this study, C57BL/6J male mice were fed a normal chow diet (NCD), a NCD plus high-NaCl diet (NCD plus NaCl), a HFD, or a HFD plus high-NaCl diet (HFD plus NaCl) for 30 weeks. No significant differences in body weight gain, insulin sensitivity, and glucose tolerance were observed between NCD-fed and NCD plus NaCl-fed mice. In contrast, body and liver weights were decreased, but the weight of epididymal white adipose tissue was increased in HFD plus NaCl-fed compared to HFD-fed mice. HFD plus NaCl-fed mice had lower plasma glucose levels in an insulin tolerance test, and showed higher plasma glucose and lower plasma insulin levels in an intraperitoneal glucose tolerance test compared to HFD-fed mice. The β-cell area and number of islets were decreased in HFD plus NaCl-fed compared to HFD-fed mice. Increased Ki67-positive β-cells, and increased expression levels of Ki67, CyclinB1, and CyclinD1 mRNA in islets were observed in HFD-fed but not HFD plus NaCl-fed mice when compared to NCD-fed mice. Our data suggest that excessive NaCl intake accompanied by a HFD exacerbates glucose intolerance, with impairment in insulin secretion caused by the attenuation of expansion of β-cell mass in the pancreas.